2020
DOI: 10.3390/jcm9113546
|View full text |Cite
|
Sign up to set email alerts
|

A 3D-CT Analysis of Femoral Symmetry—Surgical Implications

Abstract: Background: Mirroring the image of the affected side is a widely used technique for surgical planning in orthopedic surgery, especially for fractures and custom-made prostheses. Our objective is to evaluate the three-dimensional symmetry of the femurs using finite element analysis and manual alignment. Methods: Using the computed tomography of 15 patients without lower limb pathology, 30 3D biomodels of their femurs were obtained. The error obtained through image manipulation was calculated and broken down int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…The points to be chosen are those that reference the most important aspects of the study. 4 There is no previous methodology on this subject. As we wanted to compare the overall area of the articular surfaces, we selected the four cardinal points of each one, an additional point between each cardinal point and two central points in each model.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The points to be chosen are those that reference the most important aspects of the study. 4 There is no previous methodology on this subject. As we wanted to compare the overall area of the articular surfaces, we selected the four cardinal points of each one, an additional point between each cardinal point and two central points in each model.…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3] Thanks to the revolution in three-dimensional (3D) imaging and the different tools at our disposal, we can compare bone surfaces using standardized computerized processes. 4 For this study, we use the Hausdorff-Besicovitch method, which measures the morphological differences between two specific bodies in a 3D space and offers numeric analyses to quantify them. 5 This study investigates the possibility of using three different foot bones (calcaneus, cuboid bone, and lateral cuneiform bone) to replace the distal radius (DR).…”
mentioning
confidence: 99%
“…For both men and women, the left and right lower limbs maintain almost the same length, which is beneficial to maintain the balance of human bodies, and there is no significant difference between the left and right axes of the lower limbs under CT examination (Ferras-Tarrago et al, 2020). To facilitate the extraction of a femur centerline, images of the healthy side bone are used in this study.…”
Section: Centerlines Extraction Of Imn and MCmentioning
confidence: 99%
“…Moreover, patient-specific implants and instruments (PSI), such as surgical implants and surgical guides, can have advantages for patients with more severe pathologic conditions [10,11]. The most important precondition when using contralateral unaffected side bone data to repair the affected bone is similar left and right bone features [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Mopin et al reported femoral asymmetry of the human as effective for distinguishing two populations [14]. Ferràs-Tarragó et al also investigated femoral asymmetry and found symmetry between left and right healthy adult femurs [13].…”
Section: Introductionmentioning
confidence: 99%